Faktor-Faktor Yang Mempengaruhi Tingkat Kepuasan Masyarakat Terhadap Fasilitas Publik (Studi Kasus: Taman Akcaya Kota Pontianak) - B1011141081, Tri Kusumayanti (Jurnal Pembangunan dan Pemerataan, 2018)
ABSTRACTThis study aimed to find out and analyze the level of community satisfaction with the Akcaya Park facility in Pontianak City. The study uses multiple linear regression analysis with the SPSS ver. 16. The population used is the community or visitors who come to Akcaya Park in Pontianak City. The sample used was 39 respondents to visitors to the Akcaya Park in Pontianak City using the random sampling method. The results of the multiple linear regression analysis that have been done are obtained Î³ = 0.411 + 0.069 + 0.466 . The most influential independent variable on the dependent variable is the park facility variable (0.466), followed by the public service quality variable (0.411), and finally the park situation variable (0.069). The results of the t test prove that all independent variables (the quality of public services, the situation of the park, park facilities) have a positive effect on the dependent variable, namely community satisfaction. The coefficient of determination (adjusted ) obtained is 0.539. This means that 53.9% of community satisfaction is influenced by the variables of the quality of public services, the situation of the park, and the facilities of the park, the remaining 47.1% is influenced by other variables.Keyword: quality of public service, the situation of park, park facilities, and community satisfaction.ReferensiAfrial, R. (2009). Kualitas Pelayanan Publik Kecamatan Sebuah Perubahan Kedudukan dan Fungsi Camat Sebagai Perangkat Daerah. Jurnal Adminstrasi Dan Organisasi, 16(2).87-95.Arifin, Hadi Susilo. 1991. Buku Kenangan Lomba Taman Tingkat Nasioanal II 1991. Semarang: Biro Kependudukan dan Lingkungan Hidup Jawa TengahBarata, A, A. (2003). Dasar-dasar Pelayanan Prima. Jakarta: Elex Media Komputindo.Binar, R, R. (2014). Persepsi Pengunjung Taman Terhadap Tingkat Kenyamanan Taman-Taman di Kota Banjarnegara Sebagai Ruang Publik, Universitas Negera Semarang, Indonesia.Bintari, W, D (2009). Analisis Tentang Kepuasan Pengunjung Di Taman Margasatwa Semarang, Universitas Diponegoro, Indonesia.Carmona, Matthew, Tim Heath, Taner Oc, Steve Tiesdell. 2003. Public Places-Urban Spaces: The Dimensions of Urban Design. London: Architectural PressCristhoper, Lovelock. (2005). Manajemen Pemasaran Jasa, Alih bahasa Agus Widyantoro (Cetakan Pertama). Jakarta: PT Indeks.Etiningsih, E. (2016). Fungsi Taman Kota Sebagai Ruang Publik (Studi di Taman MerdekaKota Metro), Universitas Lampung, IndonesiaKantor Pekerjaan Umum dan Penataan Ruang. (2017). Kalimantan Barat. Pontianak.Nazir, M. (2015). Analisis Kepuasan Masyarakat Mengenai Pelayanan Publik Di Sistem Administrasi Manunggal Satu Atap (SAMSAT) Kota Samarinda. Jurnal Ilmu Komunikasi, Vol. 3. No. 1.Nugraheni, Z, A, A (2015). Analisis Kepuasan Masyarakat Terhadap Pelayanan Publik Berdasarkan Indeks Kepuasan Masyarakat di Kantor Kecamatan Mungkid KabupatenMagelang,Universitas Negeri Yogyakarta, Indonesia.Pasolong, Harbani. (2010). Kepemimpinan Birokrasi. Bandung: Alfabeta.Putra, D, G, Ratih Nur Pratiwi, Trisnawati. (2012). Pengaruh Kualitas Pelayanan Terhadap Kepuasan Masyarakat (Studi pada Dinas Kependudukan dan Pencatatan Sipil Kota Blitar). Jurnal Administrasi Publik (JAP), Vol. 3. No. 12.Prasetyo, D (2009). Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pengunjung Pada Obyek Wisata Taman Rekreasi Pantai Kartini Rembang, Universitas Negeri Semarang,Indonesia.Rezha, Fahmi, Siti Rochmah, Siswidiyanto. (2012). Analisis Pengaruh Kualitas Pelayanan Publik Terhadap Kepuasan Masyarakat (Studi tentang Pelayanan Perekaman KartuTanda Penduduk Elektronik (e-KTP) di Kota Depok). Jurnal Administrasi Publik (JAP),Vol. 1. No. 5.Riduwan, 2010. Metode & Teknik Menyusun Proposal Penelitian, Bandung: Penerbit Alfabeta.Samosir, Z. Z. (2005). Pengaruh kualitas Pelayanan Terhadap Kepuasan Mahasiswa Menggunakan Perpustakan USU. Jurnal Studi Perpustakaan Dan Informasi, 1(1). 28-36.Sinambela, P.L, dkk. (2011). Reformasi Pelayanan Publik. Jakarta: Bumi Aksara.Sugiyono. 2003. Metode Penelitian Bisnis. Bandung: Alfabeta.Sukamti, Sri, Hardi utomo. (2015). Analisis Indeks Kepuasan Masyarakat (IKM) Pada Pelayanan Publik Di Puskesmas Kalicacing Kota Salatiga. Jurnal Among Makarti, Vol.8. No. 15. Juli.Tjiptono, Fandy, Anastasia Diana. (2003). Total Quality Management. Yogyakarta: Andi.Tjiptono, Fandy, Gregorius Chandra. (2005). Service, Quality & Satisfaction. Yogyakarta:Andi.WebsiteAnitahidayanti. (2014). Definisi Dan Ruang Lingkup sararana dan prasarana. Diakses dari: http://anitahidayantii.blogspot.co.id/2014/09/definisi-dan-ruang-lingkup sarana-dan.html